2022
DOI: 10.1108/ijopm-10-2021-0627
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing realized absorptive capacity as the gateway to sustainable supply chain management

Abstract: PurposeCompanies' ability to build sustainable supply chains and achieve strategic sustainability objectives largely depends on their supply network characteristics and the nature of the relationships with strategic suppliers. This poses the question of how purchasing departments can help to translate this sustainability commitment into performance benefits. The authors focus the attention on buyer-supplier information sharing practices and study how the availability of information interplays with the purchasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 157 publications
(394 reference statements)
0
24
0
Order By: Relevance
“…As displayed in Table 1, all but one of the included studies use a survey methodology to establish causal links between the function's absorptive capacity and performance (e.g. Difrancesco et al, 2022;Lin et al, 2016) or to evaluate how external information availability impacts a function's absorptive capacity (e.g. Bogers and Lhuillery, 2011;Patrucco et al, 2017;Difrancesco et al, 2022).…”
Section: Quality Functions' Use Of Customer Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…As displayed in Table 1, all but one of the included studies use a survey methodology to establish causal links between the function's absorptive capacity and performance (e.g. Difrancesco et al, 2022;Lin et al, 2016) or to evaluate how external information availability impacts a function's absorptive capacity (e.g. Bogers and Lhuillery, 2011;Patrucco et al, 2017;Difrancesco et al, 2022).…”
Section: Quality Functions' Use Of Customer Feedbackmentioning
confidence: 99%
“…As displayed in Table 1, all but one of the included studies use a survey methodology to establish causal links between the function's absorptive capacity and performance (e.g. Difrancesco et al. , 2022; Lin et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…3 presents the performance implications of blockchain technology implementation across the supply chain processes. These performance implications are derived primarily from case studies' analyses and supported by the literature (e.g., Di Vaio and Varriale 2020 ; Kumar et al 2021 ; Difrancesco et al 2022 ).…”
Section: A Blockchain-enhanced Supply Chain Performance Frameworkmentioning
confidence: 98%
“…Lastly, it is also found that only a few studies include reverse logistics and sustainability aspects. Given the increasing relevance of sustainability within supply chains (Di Vaio and Varriale 2020 ; Ada et al 2021 ; Kumar et al 2021 ; Difrancesco et al 2022 ), it is evident that this represents a significant gap that urges to be addressed.…”
Section: Literature Review and Contributionmentioning
confidence: 99%